The role of structured exercise interventions on cognitive function in older individuals with stable Chronic Obstructive Pulmonary Disease: A scoping review - Eastus, Caroline C.; Baez, Daniel E.; Buckley, Maria L.; Lee, Jungeun; Adami, Alessandra (Frontiers in Rehabilitation Sciences, 2022)
A decline in cognitive performance has been associated with disease severity, exacerbations rate, presence of comorbidities, and low activity level in people with chronic obstructive pulmonary disease (COPD). Participation in exercise programs appears to have neuroprotective effects and to improve cognitive performance in older people. The present work undertook a scoping review of the effects of exercise-based interventions on cognitive function in older individuals with stable COPD. METHODS. The methodological framework for scoping review was used and electronic searches of five databases performed. Original research and observational studies published between January 2010 and December 2021, administering exercise-based interventions and cognitive function evaluation, were included. RESULTS. Of 13 full-text manuscripts assessed for eligibility, five were allocated to analysis. Three studies administered exercise training as part of pulmonary outpatient rehabilitation program (PR), one as inpatient PR. The fifth study proposed a structured training intervention in which either aerobic or a combination with resistance exercises was included. Twelve different cognitive function screening tools were used across the five studies. Results extracted were based on 245 COPD patients (33% female) with moderate to very-severe lung obstruction. Interventions lasted between 12 and 36 sessions. Studies reported positive trends to significant improvements after intervention in different cognitive function domains: global cognition (1 to 13.6%), immediate (-0.7 to 14.3%) and delayed (9.1 to 16.3%) recall ability, cognitive flexibility (8%), verbal fluency (3 to 14%), attention (-3 to 5.1%), abstract reasoning (2.5 to 6.2%%), praxis ability (6.5 to 12.1%). CONCLUSIONS. Exercise-based interventions improve several areas of cognitive function in stable COPD patients. However, the magnitude of gain varies among studies, and this is possibly due to the heterogeneity of tests used. Future research is needed to validate the optimal battery of screening tests, and support the definition of guidelines for cognitive function evaluation in COPD. In addition, cognitive tests’ ability to determine functional status is important in PR setting, wherein patients are provided with a considerable amount of practical information to apply in the daily management of COPD. Further studies should define strategies to provide adequate assistance in disease management to cognitive impaired COPD patients.